PENGARUH PAPARAN GAS KLORIN DENGAN UMUR TERHADAP KEJADIAN GANGGUAN PENGHIDU PADA PEKERJA PABRIK TEKSTIL - , STEVANO JEVON VALDANO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background:Nose is one of the human sense organ to do the olfactory function . The olfactory function also works as the defense system of the body. Chemical hazard exposure, like Chlorine, will disturb the olfactory function if the concentration is exceeding the limit. Age is also one of the factor that influences the olfactory function. Objectives:To understand whether chlorine exposure and age can affect the olfactory organ, as well as which one has affect the olfactory organ the most. Method:This is a cross-sectional study. Sample collection was done by doing an ENT test and also olfactory dysfunction test to the textile workers. Result:The subjects exposed to chlorine has 5 times chance of having an olfactory dysfunction. This means that the probability of having an olfactory dysfunction in the exposed ones is as big as 83,33% than the unexposed ones. While for the subjects with the age of â¥55 year-old has 4,5 chance of having an olfactory dysfunction. This also means that the probability of having an olfactory dysfunction in this group is as big as 81,81% than the unexposed ones. Based on the analysis of these datas, can be concluded that nothing has affected the olfactory function the most. Conclusion:Chlorine exposure and aging can cause an olfactory dysfunction, but none of them has affecting the disease the most.